P195 Usefulness of transabdominal ultrasonography in assessing ulcerative colitis. (16th January 2018) - Kinoshita, K; Katsurada, T; Nishida, M; Omotehara, S; Onishi, R; Mabe, K; Onodera, A; Sato, M; Eto, K; Suya, M; Maemoto, A; Hasegawa, T; et al.
Abstract: Background: Transabdominal ultrasonography (US) has been reported to be a useful tool for evaluating ulcerative colitis (UC). Although several studies have evaluated the accuracy of US for assessing UC compared with colonoscopy, most of the aforementioned studies were retrospective, and were performed at a single center with only a limited number of expert sonographers. Thus, US has not yet come into general, widespread use for assessing UC. The aim of this prospective, multicentre study was therefore to evaluate the usefulness of US for assessing UC, compared with colonoscopy. Methods: All consecutive patients with an established diagnosis of ulcerative colitis were prospectively recruited at five facilities in Japan from June 2013 to September 2016. All patients underwent US and CS within 2 days at five facilities. Six colonic segments (cecum, ascending colon, right-sided transverse colon, left-sided transverse colon, descending colon, sigmoid colon), and the rectum were examined by US and CS of each other. US was performed by 24 sonographers from different facilities. All still images and movie clips were analysed and interpreted in a consensus manner by two registered sonographers who were blinded to the patients' clinical information and to CS findings. US severity was graded 1–4, regarding bowel wall thickness, stratification, and ulceration. CS severity was also graded 1–4, according to the Matts' endoscopic classification. Concordance between US and CS grades was assessed for all colonic segments using kappa (κ) statistics. To verify the reproducibility of US grading, interobserver agreement was calculated using κ statistics between interpretations of each sonographer and two consensus readers considering the US grade. Results: A total of 156 patients were eligible for this study. We achieved moderate concordance between US and CS grades in all colonic segments (weighted κ = 0.55). In each colonic segment, concordance rate was moderately agreement (weighted κ between 0.44 and 0.56), while rectum was slightly agreement (weighted κ = 0.33). The interobserver agreement between consensus readers and each sonographer was substantial agreement for all colonic segments (weighted κ = 0.73; 95% CI, 0.65–0.80). Conclusions: This prospective multicentre study showed moderately concordance between US and CS in assessing the disease activity of UC. Moreover, interobserver agreement between central readers and each sonographer was good. Therefore, we suggest that more general and widespread use of US could be applied in day-to-day clinical practice.